Tìm x
a, \(2x+3-\sqrt{x+1}=4\)
b, \(x^2+\sqrt{x+7}=7\)
c, \(4x-2\sqrt{4x+1}=6\)
giải pt :
a, \(\left(x^2+2\right)^2+4\left(x+1\right)^3+\sqrt{x^2+2x+5}=\left(2x-1\right)^2+2\)
b, \(\sqrt{4x^2+x+6}=4x-2+7\sqrt{x+1}\)
c, \(\sqrt{x-2}-\sqrt{x+2}=2\sqrt{x^2-4}-2x+2\)
giải pt :
a, \(\sqrt{x-\sqrt{x^2-1}}+\sqrt{x+\sqrt{x^2-1}}=2\)
b, \(\left(x^2+2\right)^2+4\left(x+1\right)^3+\sqrt{x^2+2x+5}=\left(2x-1\right)^2+2\)
c, \(\sqrt{4x^2+x+6}=4x-2+7\sqrt{x+1}\)
d, \(\sqrt{x-2}-\sqrt{x+2}=2\sqrt{x^2-4}-2x+2\)
Tìm x
\(a.\dfrac{\sqrt{5x+7}}{x+3}=4\)
\(b.\left(7+\sqrt{x}\right).\left(8-\sqrt{x}\right)=11+x\)
\(c.\sqrt{2x^2+2-4x}=6\)
2.tìm x
a)\(\sqrt{x^2-6x+9}\)
b)\(\sqrt{x^2-2x+1}\)
c)\(\sqrt{4x+12}-3\sqrt{x+3}+7\sqrt{9x+27}=20\)
d)\(\sqrt{4x+20}+3\sqrt{\dfrac{x-5}{9}}-\dfrac{1}{3}\sqrt{9x-45}=6\)
a) \(\sqrt{x^2-6x+9}\)
\(=\sqrt{\left(x^2-2.x.3+3^2\right)}\)
\(=\sqrt{\left(x-3\right)^2}\) ≥0,∀x
⇒x∈\(R\)
b) \(\sqrt{x^2-2x+1}\)
\(=\sqrt{\left(x^2-2.x.1+1^2\right)}\)
\(=\sqrt{\left(x-1\right)^2}\) ≥0,∀x
⇒x∈\(R\)
1)\(7\sqrt{3x-7}+\left(4x-7\right)\sqrt{7-x}=32\)
2)\(4x^2-11x+6=\left(x-1\right)\sqrt{2x^2-6x+6}\)
3)\(9+3\sqrt{x\left(3-2x\right)}=7\sqrt{x}+5\sqrt{3-2x}\)
4)\(\sqrt{2x^2+4x+7}=x^4+4x^3+3x^2-2x-7\)
5)\(\frac{6-2x}{\sqrt{5-x}}+\frac{6+2x}{\sqrt{5+x}}=\frac{8}{3}\)
6)\(2\left(5x-3\right)\sqrt{x+1}+\left(x+1\right)\sqrt{3-x}=3\left(5x+1\right)\)
7)\(\sqrt{7x+7}+\sqrt{7x-6}+2\sqrt{49x^2+7x-42}=181-14x\)
Giải PT:
a) \(\sqrt{11+6\sqrt{2}}\) = \(\sqrt{2x^2-6x\sqrt{2}+9}\)
b) \(\sqrt{4x^2+4x\sqrt{7}+7}\) - \(\sqrt{8-2\sqrt{7}}\) = 0
c) \(\sqrt{x^2}\) = x
d) \(\sqrt{x^2-2x+1}\) = x-1
c: Ta có: \(\sqrt{x^2}=x\)
\(\Leftrightarrow\left|x\right|=x\)
hay \(x\ge0\)
d: Ta có: \(\sqrt{x^2-2x+1}=x-1\)
\(\Leftrightarrow\left|x-1\right|=x-1\)
hay \(x\ge1\)
giải pt :
a, \(\left(2x-6\right)\sqrt{x+4}-\left(x-5\right)\sqrt{2x+3}=3\left(x-1\right)\)
b, \(\left(4x+1\right)\sqrt{x+2}-\left(4x-1\right)\sqrt{x-2}=21\)
c, \(\left(4x+2\right)\sqrt{x+1}-\left(4x-2\right)\sqrt{x-1}=9\)
d, \(\left(2x-4\right)\sqrt{3x-2}+\sqrt{x+3}=5x-7+\sqrt{3x^2+7x-6}\)
Tìm điều kiện có nghĩa:
1) \(-\dfrac{1}{\sqrt{a+2}}\)
2) \(\sqrt{\dfrac{3}{\left(x-2\right)^2}}\)
3) \(\sqrt{\dfrac{-3}{a^2-4a+4}}\)
4) \(\sqrt{\dfrac{2}{x^2+2x+2}}\)
5) \(\sqrt{\dfrac{-3}{x^2-4x+5}}\)
6) \(\sqrt{\dfrac{-4}{x^2-1}}\)
7) \(\sqrt{\dfrac{x+1}{x-2}}\)
8) \(\sqrt{\dfrac{x-2}{x+3}}\)
1: ĐKXĐ: \(a>-2\)
2: ĐKXĐ: \(x\ne2\)
3: ĐKXĐ: \(a\in\varnothing\)
1)
\(-\dfrac{1}{\sqrt{a+2}}\) có nghĩa khi \(\sqrt{a+2}>0\)
=>a+2>0
a>-2
2)
\(\sqrt{\dfrac{3}{\left(x-2\right)^2}}=\dfrac{\sqrt{3}}{\sqrt{\left(x-2\right)^2}}\)
mà \(\left(x-2\right)^2>0=>\sqrt{\left(x-2\right)^2}>0vớimọix\)
3)
\(\sqrt{\dfrac{-3}{a^2-4a+4}}=\sqrt{\dfrac{-3}{\left(a-2\right)^2}}cónghĩakhi\left(a-2\right)^2< 0mà\left(a-2\right)^2>0=>biểuthứckocónghĩavớimọia\)
a) \(-\dfrac{1}{\sqrt{a+2}}\Rightarrow\sqrt{a+2}>0\Leftrightarrow a>-2\)
b) \(\sqrt{\dfrac{3}{\left(x-2\right)^2}}\Rightarrow x-2\ne0\Leftrightarrow x\ne2\)
c) \(\sqrt{\dfrac{-3}{a^2-4a+4}}\Rightarrow a^2-4a+4< 0\Leftrightarrow a^2-4a< -4\)
d) \(\sqrt{\dfrac{2}{x^2+2x+2}}\Rightarrow x^2+2x+2>0\Leftrightarrow x^2+2x>-2\)
e) \(\sqrt{\dfrac{-3}{x^2-4x+5}}\Rightarrow x^2-4x+5< 0\Leftrightarrow x^2-4x< -5\)
f) \(\sqrt{\dfrac{-4}{x^2-1}}\Rightarrow x^2-1< 0\Rightarrow x^2< 1\Rightarrow x< 1\)
2 câu cuối do lỗi nên mk ko gõ cth được
Giải phương trình:
1. \(\sqrt{2x^2+4x+7}=x^4+4x^3+3x^2-2x-7\)
2. \(\dfrac{4}{x}+\sqrt{x-\dfrac{1}{x}}=x+\sqrt{2x-\dfrac{5}{x}}\)
3. \(\dfrac{6-2x}{\sqrt{5-x}}+\dfrac{6+2x}{\sqrt{5+x}}=\dfrac{8}{3}\)
4. \(x^2+1-\left(x+1\right)\sqrt{x^2-2x+3}=0\)
5. \(2\sqrt{2x+4}+4\sqrt{2-x}=\sqrt{9x^2+16}\)
6. \(\left(2x+7\right)\sqrt{2x+7}=x^2+9x+7\)